A high thermal conductivity electronic pressure-sensitive adhesive and its preparation method and use method

A high thermal conductivity electronic pressure-sensitive adhesive, made from natural rubber, polyurethane rubber, and thermal conductive fillers, addresses overheating and bonding issues in smart devices by enhancing thermal conductivity and insulation, ensuring reliable device operation.

CN116254081BActive Publication Date: 2024-12-17ENPING YINGJIAFENG ADHESIVE PROD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310027802.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-09
Publication Date
2024-12-17
Estimated Expiration
2043-01-09

AI Technical Summary

Technical Problem

Existing adhesives used in smart devices lack ideal thermal conductivity and insulation, leading to overheating issues and potential device failures due to poor bonding and insulation properties, especially in precision electronic equipment.

Method used

A high thermal conductivity electronic pressure-sensitive adhesive composed of natural rubber, polyurethane rubber, SIS elastomer, acrylate modified monomers, petroleum resin, and thermal conductive fillers, along with a specific preparation method, to enhance bonding, thermal conductivity, and insulation.

Benefits of technology

The adhesive achieves excellent adhesive properties, high thermal conductivity, and insulation, addressing overheating and device failure issues, with improved initial adhesion, aging resistance, and temperature resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004045887850000101
    Figure BDA0004045887850000101
  • Figure BDA0004045887850000111
    Figure BDA0004045887850000111
Patent Text Reader

Abstract

A high thermal conductivity electronic pressure-sensitive adhesive and its preparation method and use method, including 80-100 parts of natural rubber, 20-40 parts of polyurethane rubber, 20-40 parts of SIS elastomer, 3-8 parts of acrylate modified monomer, 30-50 parts of petroleum resin, 10-20 parts of thermal conductive filler, 0.3-0.8 parts of benzoyl peroxide, cross-linking agent, toluene, ethyl acetate and antioxidant; the raw material of the thermal conductive filler is selected from one or more combinations of silicon carbide, aluminum carbide, silicon dioxide and aluminum oxide, the acrylate modified monomer includes 2-ethylhexyl acrylate, methyl methacrylate and acrylic acid, and the polyurethane rubber is a polyether polyurethane elastomer material. The pressure-sensitive adhesive of the present invention has good thermal conductivity and insulation, as well as good bonding performance, aging resistance and high and low temperature resistance, and can be applied to electronic components that require heat-resistant heat dissipation insulation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of adhesives, and in particular to a high thermal conductivity electronic pressure-sensitive adhesive and a preparation method and a use method thereof. Background Art

[0002] With the increasing intelligence of manufacturing and home life, as well as the development of modern electronic information technology, smart devices are playing an increasingly important role in production and life, and these smart devices are developing in the direction of refinement, integration and miniaturization. Therefore, in their design and manufacturing, factors such as thermal management, dielectric loss, and lightweight in the production and use process need to be considered. In particular, the overheating problem has become a shackle restricting the development of electronic technology, and new technologies are urgently needed to solve energy consumption and heat dissipation problems. Various adhesives are used on smart devices, including some pressure-sensitive adhesive tapes used in the manufacturing and use process, which need to have corresponding functions. The thermal conductivity and insulation of existing insulating tapes on the market are not ideal, and the insulating adhesives used in precision electronic equipment require higher thermal conductivity and insulation, which is difficult to meet the requirements; and the thermal conductivity and insulation of the insulating tapes on the market mainly rely on the addition of an insulating substrate layer, rather than relying on the corresponding adhesive layer to play a role, resulting in a large thickness and limited use; some insulating tapes have better thermal conductivity and insulation, but the corresponding adhesive properties are poor, such as low initial adhesion and long-term adhesion, easy aging, etc.; some thermal conductive adhesives are mainly added by adding metal powder as thermal conductive fillers, but when precision electronic equipment is running for a long time in special environments such as shaking and bumping, the leakage of thermal conductive insulating adhesives may cause device short circuits and affect the insulation effect. Therefore, it is particularly important to develop high-insulation and high-thermal-conductivity pressure-sensitive adhesives. Summary of the invention

[0003] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a high thermal conductivity electronic pressure-sensitive adhesive with good bonding performance, thermal conductivity, and high and low temperature resistance, as well as a preparation method and a use method of the high thermal conductivity electronic pressure-sensitive adhesive.

[0004] The present invention is achieved through the following technical solutions:

[0005] A high thermal conductivity electronic pressure-sensitive adhesive comprises the following components in parts by weight: 80-100 parts of natural rubber, 20-40 parts of polyurethane rubber, 20-40 parts of SIS elastomer, 3-8 parts of acrylate modified monomer, 30-50 parts of petroleum resin, 10-20 parts of thermal conductive filler, 0.3-0.8 parts of benzoyl peroxide, a crosslinking agent, toluene, ethyl acetate and an antioxidant.

[0006] As an adhesive, natural rubber has a certain degree of self-adhesiveness. Polyurethane rubber has strong cohesive force and certain flexibility because its molecular chain contains carbamate groups, ether groups, urea groups and fatty chains, and there are hydrogen bonds between and within the molecular chains. As an adhesive, it has the characteristics of high bonding strength, high initial adhesion, storage stability, and good high and low temperature resistance. Natural rubber and polyurethane rubber are the main materials of pressure-sensitive adhesives. They have high molecular weights and certain crystallinity in their molecular chains, so they have high cohesive strength and the pressure-sensitive adhesives made of them have good holding power.

[0007] SIS (styrene-isoprene-styrene) is a medium molecular weight polymer with low modulus, easy to produce stickiness, low melt viscosity, low solution viscosity and good fluidity; petroleum resin is a medium and low molecular weight polymer as a tackifying resin. When added to the adhesive, it has a wetting effect on the adhered surface. Through surface diffusion or internal diffusion, the pressure-sensitive adhesive can produce high adhesion under certain conditions, with good initial adhesion and adhesion. These medium and low molecular weight polymers penetrate into high molecular weight rubber, which can improve the creep of molecular chains and chain segments in the entire polymer structure, and improve viscoelasticity and adhesion.

[0008] Acrylate modified monomers can undergo grafting reaction with natural rubber and SIS with unsaturated bonds under the action of initiators, thereby improving the adhesive properties (mainly the stickiness), aging resistance and high and low temperature resistance of pressure-sensitive adhesives. Adding thermal conductive fillers can significantly reduce the thermal resistance caused by contact gaps and improve the heat dissipation effect.

[0009] Furthermore, the raw material of the thermal conductive filler is selected from one or a combination of silicon carbide, aluminum carbide, silicon dioxide and aluminum oxide, and these raw materials are also excellent insulating materials.

[0010] Furthermore, the particle size of the thermal conductive filler raw material is 5-10 μm.

[0011] Furthermore, the preparation method of the thermal conductive filler is as follows: after adding 0.3-1 parts by weight of a silane coupling agent to 20-50 parts by weight of ethanol and stirring to dissolve, 100 parts by weight of a thermal conductive filler raw material is added, stirring and dispersing is continued until uniform, the pH value of the dispersion is adjusted to 10, and the dispersion is placed in a 50-60° water bath and stirred for reaction for 2-3 hours, and ultrasonically dispersed for 10-20 minutes to obtain a thermal conductive filler; the silane coupling agent is selected from one or more of bis-[3-(triethoxysilyl)-propyl]-tetrasulfide, bis-[3-(triethoxysilyl)-propyl]-disulfide, and γ-mercaptopropyltrimethoxysilane.

[0012] Furthermore, the mass content of styrene in the SIS elastomer is 15%-18%, the mass content of the diblock is 30%-60%, and the viscosity of a 25% mass concentration toluene solution at 25° C. is 700-900 mPa·s.

[0013] Furthermore, the acrylic acid ester modified monomers include 2-ethylhexyl acrylate, methyl methacrylate and acrylic acid, and 2-ethylhexyl acrylate and methyl methacrylate account for 60%-75% and 15%-30% of the total mass of all acrylic acid ester modified monomers, respectively.

[0014] Furthermore, the polyurethane rubber is a polyether polyurethane elastomer material. The petroleum resin is C5 petroleum resin, which is easily miscible with the main resin. The surface energy of the prepared pressure-sensitive adhesive is low, and it is easy to wet various solid surfaces, so the initial adhesion and bonding properties are relatively good; the tackifying resin does not contain polar groups, which can improve the insulation of the main resin; there is no or very little double bond in its molecule, which can improve the aging resistance.

[0015] Furthermore, the crosslinking agent is selected from one or more of trimethylolpropane, polyamine, and aziridine. The antioxidant is one of p-hydroxyanisole (MEHQ), 2,6-di-tert-butyl-p-cresol (BHT, 264), antioxidant 1010, antioxidant 168, and antioxidant 1076.

[0016] A method for preparing the above-mentioned high thermal conductivity electronic pressure-sensitive adhesive comprises the following steps:

[0017] (1) Natural rubber and polyurethane rubber are plasticized on an open mill respectively, and then added into a mixer for mixing. After the materials are discharged, they are left to stand for 1-2 days to obtain a mixture A.

[0018] Rubber raw materials are first plasticized to break the rubber molecular chain, reduce the molecular weight of the rubber, and improve the plasticity of the material. The breaking effect can occur both in the main chain of the macromolecule and in the side chain; after plasticization, the high molecular weight macromolecules and a small amount of gel components disappear, so the rubber can be dissolved into a uniform pressure-sensitive adhesive solution with a lower viscosity than the coating operation.

[0019] (2) Mixture A is cut into small pieces and put into a reaction device with SIS elastomer, and then toluene and part of ethyl acetate are added. After continuous stirring and slowly heating to 60-80°C to dissolve, a mixed solution of acrylic ester modified monomer and benzoyl peroxide is slowly added dropwise at a constant temperature. The addition time is controlled at 40-60 minutes. After the addition is completed, the reaction is continued for 1-2 hours, and then cooled to obtain mixture B.

[0020] (3) Add the remaining ethyl acetate to the thermal conductive filler, stir and disperse it evenly, then add the petroleum resin, cross-linking agent and antioxidant, stir and disperse and dissolve them evenly, to obtain a mixture C.

[0021] (4) Add mixed material C to mixed material B and stir evenly to obtain a high thermal conductivity and high insulation pressure-sensitive adhesive.

[0022] A method for using the above-mentioned high thermal conductivity electronic pressure-sensitive adhesive is to apply the pressure-sensitive adhesive liquid on a PET film through an applicator, and then place it in an oven at 110-140°C for curing for 3-5 minutes, and then cut it into strips to obtain a high thermal conductivity and high insulation pressure-sensitive adhesive tape. The pressure-sensitive adhesive liquid contains a certain amount of cross-linking agent, which can be cured and formed at a certain temperature.

[0023] The present invention uses polymer materials with different properties such as natural rubber, polyurethane rubber and SIS elastomer to be compounded as the main material of the pressure-sensitive adhesive, which can integrate the properties of various different types of materials to achieve a good balance of various bonding properties of the adhesive, and further modify the main material by adding acrylic ester modified monomers and petroleum resins, and finally achieve good bonding properties, aging resistance and high and low temperature resistance of the adhesive; by adding thermal conductive fillers to the mixture, the thermal conductivity of the pressure-sensitive adhesive can be improved, and it can be applied to some electronic components that require heat resistance and heat dissipation; the combination of multiple materials also enables the overall adhesive system to have excellent insulation properties, and can be applied to occasions that require insulation. DETAILED DESCRIPTION

[0024] A high thermal conductivity electronic pressure-sensitive adhesive comprises the following components in parts by weight: 80-100 parts of natural rubber, 20-40 parts of polyurethane rubber, 20-40 parts of SIS elastomer, 3-8 parts of acrylate modified monomer, 30-50 parts of petroleum resin, 10-20 parts of thermal conductive filler, 0.3-0.8 parts of benzoyl peroxide, crosslinking agent, toluene, ethyl acetate and antioxidant. Toluene and ethyl acetate can be adjusted according to the viscosity of the system, and the antioxidant is used in an appropriate amount.

[0025] The raw material of the thermal conductive filler is selected from one or a combination of silicon carbide, aluminum carbide, silicon dioxide and aluminum oxide. The particle size of the raw material of the thermal conductive filler is 5-10 μm.

[0026] The preparation method of the thermal conductive filler is as follows: 0.3-1 parts by weight of a silane coupling agent is added to 20-50 parts by weight of ethanol and stirred to dissolve, then 100 parts by weight of a thermal conductive filler raw material is added, and the mixture is stirred and dispersed evenly, and the pH value of the dispersion is adjusted to 10, and the mixture is placed in a 50-60° water bath and stirred for reaction for 2-3 hours, and ultrasonically dispersed for 10-20 minutes to obtain the thermal conductive filler; the silane coupling agent is selected from one or more of bis-[3-(triethoxysilyl)-propyl]-tetrasulfide, bis-[3-(triethoxysilyl)-propyl]-disulfide, and γ-mercaptopropyltrimethoxysilane.

[0027] The mass content of styrene in the SIS elastomer is 15%-18%, the mass content of the diblock is 30%-60%, and the viscosity of a 25% mass concentration toluene solution at 25° C. is 700-900 mPa·s.

[0028] The acrylic acid ester modified monomers include 2-ethylhexyl acrylate, methyl methacrylate and acrylic acid, wherein 2-ethylhexyl acrylate and methyl methacrylate account for 60%-75% and 15%-30% of the total mass of all acrylic acid ester modified monomers respectively.

[0029] The polyurethane rubber is a polyether polyurethane elastomer material, such as UR101 type polyether mixing type polyurethane rubber. The petroleum resin is C5 petroleum resin, such as relevant products of Dow Chemical Company and Exxon Company.

[0030] The cross-linking agent is selected from one or more of trimethylolpropane, polyamine, and aziridine. The antioxidant is one of p-hydroxyanisole (MEHQ), 2,6-di-tert-butyl-p-cresol (BHT, 264), antioxidant 1010, antioxidant 168, and antioxidant 1076.

[0031] A method for preparing the above-mentioned high thermal conductivity electronic pressure-sensitive adhesive comprises the following steps:

[0032] (1) Natural rubber and polyurethane rubber are plasticized on an open mill respectively, and then added into a mixer for mixing. After the materials are discharged, they are left to stand for 1-2 days to obtain a mixture A.

[0033] (2) Mixture A is cut into small pieces and put into a reaction device with SIS elastomer, and then toluene and part of ethyl acetate are added. After continuous stirring and slowly heating to 60-80°C to dissolve, a mixed solution of acrylic ester modified monomer and benzoyl peroxide is slowly added dropwise at a constant temperature. The addition time is controlled at 40-60 minutes. After the addition is completed, the reaction is continued for 1-2 hours, and then cooled to obtain mixture B.

[0034] (3) Add the remaining ethyl acetate to the thermal conductive filler, stir and disperse it evenly, then add the petroleum resin, cross-linking agent and antioxidant, stir and disperse and dissolve them evenly, to obtain a mixture C.

[0035] (4) Add mixed material C to mixed material B and stir evenly to obtain a high thermal conductivity and high insulation pressure-sensitive adhesive.

[0036] A method for using the above-mentioned high thermal conductivity electronic pressure-sensitive adhesive is to coat the pressure-sensitive adhesive liquid on a PET film through an applicator, and then place it in an oven at 110-140° C. for curing for 3-5 minutes, and then cut it into strips to obtain a high thermal conductivity and high insulation pressure-sensitive adhesive tape.

[0037] Example 1

[0038] A high thermal conductivity electronic pressure-sensitive adhesive comprises the following components in parts by weight: 100 parts of natural rubber, 30 parts of polyurethane rubber, 30 parts of SIS elastomer, 7 parts of acrylate modified monomer, 40 parts of petroleum resin, 16 parts of thermal conductive filler, 0.6 parts of benzoyl peroxide, a crosslinking agent, toluene, ethyl acetate and an antioxidant.

[0039] The raw material of the thermal conductive filler is a combination of silicon carbide and aluminum oxide, and the particle size thereof is 5-10 μm.

[0040] The grade of the SIS elastomer is 1250, the mass content of styrene is 16%, the mass content of diblock is 50%, and the viscosity of a 25% mass concentration toluene solution at 25° C. is 700 mPa·s.

[0041] The acrylic ester modified monomer includes 70% by weight of 2-ethylhexyl acrylate, 25% by weight of methyl methacrylate and 5% by weight of acrylic acid.

[0042] Example 2

[0043] A high thermal conductivity electronic pressure-sensitive adhesive comprises the following components in parts by weight: 90 parts of natural rubber, 25 parts of polyurethane rubber, 40 parts of SIS elastomer, 6 parts of acrylate modified monomer, 45 parts of petroleum resin, 15 parts of thermal conductive filler, 0.5 parts of benzoyl peroxide, a crosslinking agent, toluene, ethyl acetate and an antioxidant.

[0044] The raw material of the thermal conductive filler is selected from a combination of aluminum carbide and silicon dioxide, and the particle size thereof is 5-10 μm.

[0045] The grade of the SIS elastomer is 1170, the mass content of styrene is 17%, the mass content of diblock is 67%, and the viscosity of a 25% mass concentration toluene solution at 25° C. is 800 mPa·s.

[0046] The acrylic ester modified monomer includes 65% by weight of 2-ethylhexyl acrylate, 30% by weight of methyl methacrylate and 5% by weight of acrylic acid.

[0047] Example 3

[0048] A high thermal conductivity electronic pressure-sensitive adhesive comprises the following components in parts by weight: 80 parts of natural rubber, 30 parts of polyurethane rubber, 35 parts of SIS elastomer, 5 parts of acrylate modified monomer, 40 parts of petroleum resin, 13 parts of thermal conductive filler, 0.4 parts of benzoyl peroxide, a crosslinking agent, toluene, ethyl acetate and an antioxidant.

[0049] The raw material of the thermal conductive filler is selected from a combination of silicon carbide, aluminum carbide and aluminum oxide, and the particle size thereof is 5-10 μm.

[0050] The grade of the SIS elastomer is 1250L, the mass content of styrene is 16%, the mass content of diblock is 50%, and the viscosity of a 25% mass concentration toluene solution at 25° C. is 900 mPa·s.

[0051] The acrylic ester modified monomer includes 75% by weight of 2-ethylhexyl acrylate, 18% by weight of methyl methacrylate and 7% by weight of acrylic acid.

[0052] Comparative Example 1

[0053] The rest is the same as Example 1, except that no polyurethane rubber is added.

[0054] Comparative Example 2

[0055] The rest is the same as Example 1, except that no SIS elastomer is added.

[0056] Comparative Example 3

[0057] The rest is the same as Example 3, except that no thermal conductive filler is added.

[0058] Comparative Example 4

[0059] The common electronic and electrical insulating tape available on the market has a base material of polyimide PI and an adhesive layer of silicone pressure-sensitive adhesive.

[0060] Performance Test:

[0061] The pressure-sensitive adhesive tapes prepared in Examples 1-3 and Comparative Examples 1-4 were tested for 180° peel strength using the test method ASTM D3330, for initial adhesion using the test method ASTM D3121, for sustained adhesion using the test method ASTM D3654, for thermal conductivity using a thermal resistance tester by a steady-state heat flow method using the test standard ASTM D5470, and for insulation using the test method ASTM D149. The results are shown in Table 1.

[0062] Table 1 Performance test results of Examples 1-3 and Comparative Examples 1-4

[0063]

[0064]

[0065] From the performance test results in Table 1, it can be seen that the initial adhesion of the pressure-sensitive adhesive of the present invention is comparable to that of ordinary insulating tapes on the market, the holding force and 180° peeling force are better than ordinary insulating tapes on the market, and the thermal conductivity and insulation performance are better than ordinary insulating tapes on the market. From the data comparing Example 1 with Comparative Examples 1 and 2, it can be found that the addition of polyurethane rubber and SIS elastomer can improve the comprehensive bonding performance of the adhesive, including peeling force and holding force, and the electrical insulation performance is also improved to varying degrees; from the data comparing Example 3 with Comparative Example 3, it can be found that the addition of thermally conductive fillers in this application significantly improves the thermal conductivity of the pressure-sensitive adhesive, and also improves the electrical insulation performance and bonding performance to varying degrees.

[0066] Therefore, the high thermal conductivity pressure-sensitive adhesive of the present application not only has excellent adhesive properties, but also has excellent thermal conductivity and insulation properties. The pressure-sensitive tape of the present application has multiple uses and can be applied to different scenarios, such as electronic devices that require heat-resistant, thermally conductive and insulating properties.

[0067] The above detailed description is a specific description of a feasible embodiment of the present invention. The embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not deviate from the present invention should be included in the patent scope of this case.

Claims

1. A high thermal conductivity electronic pressure-sensitive adhesive, characterized in that: The invention comprises the following components in parts by weight: 80-100 parts of natural rubber, 20-40 parts of polyurethane rubber, 20-40 parts of SIS elastomer, 3-8 parts of acrylic modified monomer, 30-50 parts of petroleum resin, 10-20 parts of thermal conductive filler, 0.3-0.8 parts of benzoyl peroxide, crosslinking agent, toluene, ethyl acetate and antioxidant; The raw material of the thermal conductive filler is selected from one or a combination of silicon carbide, aluminum carbide, silicon dioxide and aluminum oxide; the particle size of the raw material of the thermal conductive filler is 5-10 μm; The preparation method of the thermal conductive filler is as follows: 0.3-1 parts by weight of a silane coupling agent is added to 20-50 parts by weight of ethanol and stirred to dissolve, then 100 parts by weight of a thermal conductive filler raw material is added, and the mixture is stirred and dispersed uniformly, and the pH value of the dispersion is adjusted to 10, and the mixture is placed in a 50-60° C. water bath and stirred for reaction for 2-3 hours, and ultrasonically dispersed for 10-20 minutes to obtain the thermal conductive filler; the silane coupling agent is selected from one or more of bis-[3-(triethoxysilyl)-propyl]-tetrasulfide, bis-[3-(triethoxysilyl)-propyl]-disulfide, and γ-mercaptopropyltrimethoxysilane; The mass content of styrene in the SIS elastomer is 15%-18%, the mass content of the diblock is 30%-60%, and the viscosity of a 25% mass concentration toluene solution at 25° C. is 700-900 mPa·s; The acrylic acid ester modified monomers include 2-ethylhexyl acrylate, methyl methacrylate and acrylic acid, wherein 2-ethylhexyl acrylate and methyl methacrylate account for 60%-75% and 15%-30% of the total mass of all acrylic acid ester modified monomers, respectively; The method for preparing the high thermal conductivity electronic pressure-sensitive adhesive comprises the following steps: The natural rubber and the polyurethane rubber are respectively plasticized on an open mill, and then added into a mixer for mixing, and the materials are left to stand for 1-2 days after being discharged to obtain a mixture A; Mixture A is cut into small pieces and put into a reaction device with SIS elastomer, then toluene and part of ethyl acetate are added, and the mixture is slowly heated to 60-80°C with continuous stirring to dissolve, and then the mixture of acrylic modified monomer and benzoyl peroxide is slowly added dropwise at a constant temperature, and the addition time is controlled within 40-60 minutes. After the addition is completed, the reaction is continued for 1-2 hours, and then cooled to obtain mixture B; Add the remaining ethyl acetate to the thermal conductive filler, stir and disperse it evenly, then add petroleum resin, crosslinking agent and antioxidant, stir and disperse and dissolve them evenly to obtain a mixture C; Add mixed material C into mixed material B and stir evenly to obtain a high thermal conductivity and high insulation pressure-sensitive adhesive.

2. A high thermal conductivity electronic pressure-sensitive adhesive according to claim 1, characterized in that: The polyurethane rubber is a polyether polyurethane elastomer material, and the petroleum resin is a C5 petroleum resin.

3. The high thermal conductivity electronic pressure-sensitive adhesive according to claim 1, characterized in that: The cross-linking agent is selected from one or more of trimethylolpropane, polyamine, and aziridine; the antioxidant is one of p-hydroxyanisole (MEHQ), 2,6-di-tert-butyl-p-cresol (BHT, 264), antioxidant 1010, antioxidant 168, and antioxidant 1076.

4. A method for using the high thermal conductivity electronic pressure-sensitive adhesive according to any one of claims 1 to 3, characterized in that: The pressure-sensitive adhesive liquid is coated on the PET film through an applicator, and then placed in an oven at 110-140°C for curing for 3-5 minutes. After stripping, a high thermal conductivity and high insulation pressure-sensitive adhesive tape is obtained.